THE RELATIONSHIP BETWEEN GESTATIONAL AGE AND LBW WITH HYPERBILIRUBIN INCIDENCE IN NEWBORN BABIES AT ANGGABERI COMMUNITY HEALTH CENTER - Tety Ripursari; Jumarni; Nur Yeny Hidajaturrokhmah; Agus Santoso (Master of Public Health Program Universitas STRADA Indonesia, 2025)
Hyperbilirubinemia in premature babies has a higher incidence. Gestational age is the period of time since the fertilization of the egg until the birth of the baby. LBW is a condition where a newborn baby weighs less than 2,500 grams. The purpose of this study was to determine the relationship between gestational age and LBW with the incidence of hyperbilirubinemia in newborns. This study used a descriptive correlation survey research design with a Cross Sectional approach. The sampling technique used purposive sampling with a sample size of 40. The results of the study: most of the gestational ages were aterm with no hyperbilirubinemia 18 respondents (69.2%), almost all of them were LBW with hyperbilirubinemia 17 respondents (77.3%), The results of the chi-square test showed gestational age with the incidence of Hyperbilirubin p-value (0.011), LBW with the incidence of hyperbilirubin p-value (0.000) which means there is a relationship between gestational age and LBW with the incidence of hyperbilirubinemia in newborns at the Anggaberi Health Center. It is expected that pregnant women routinely check their pregnancy with a midwife or hospital. Keywords: Gestational Age, Low Birth Weight, Hyperbilirubinemia